2020
DOI: 10.1002/pro.3812
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the nucleotide hydrolase BlsM: Implication of its substrate specificity

Abstract: Biosynthesis of the peptidyl nucleoside antifungal agent blasticidin S in Streptomyces griseochromogenes requires the hydrolytic function of a nucleotide hydrolase, BlsM, to excise the free cytosine from the 5′‐monophosphate cytosine nucleotide. In addition to its hydrolytic activity, interestingly, BlsM has also been shown to possess a novel cytidine deaminase activity, converting cytidine, and deoxycytidine to uridine and deoxyuridine. To gain insight into the substrate specificity of BlsM and the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Qng1 adopts an HhH-glycosylase fold, prefers Q-5′MP as substrate, is metal independent and functions as a monomer; while QueK is a homotrimeric protein with a preference for Q as substrate and belongs to the Ca 2+ -dependent nucleoside hydrolase (NH) superfamily which use a Rossmann-fold catalytic core and a bound Ca 2+ ion to coordinate the substrate ribose and nucleophilic water molecule (single-displacement mechanism) ( 70 ). Further, Qng1 is structurally distinct from all known nucleotide hydrolases, which are all Rossmann fold-containing multimeric proteins, including the ppnN family of pyrimidine/purine-5′-nucleotide nucleosidases ( 71 ), the LOG family of cytokinin riboside-5′-monophosphate phosphoribohydrolases ( 72 ), 2′-deoxyguanosine-5′-monophosphate hydrolase DNPH1 ( 73 ), and cytosine-5′-monophosphate hydrolase Blsm ( 74 ) and hydroxyl-methyl cytosine-5′-monophosphate hydrolase MilB ( 75 ) involved in the biosynthesis of the peptidyl nucleoside antifungal agents blasticidin and mildiomycin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Qng1 adopts an HhH-glycosylase fold, prefers Q-5′MP as substrate, is metal independent and functions as a monomer; while QueK is a homotrimeric protein with a preference for Q as substrate and belongs to the Ca 2+ -dependent nucleoside hydrolase (NH) superfamily which use a Rossmann-fold catalytic core and a bound Ca 2+ ion to coordinate the substrate ribose and nucleophilic water molecule (single-displacement mechanism) ( 70 ). Further, Qng1 is structurally distinct from all known nucleotide hydrolases, which are all Rossmann fold-containing multimeric proteins, including the ppnN family of pyrimidine/purine-5′-nucleotide nucleosidases ( 71 ), the LOG family of cytokinin riboside-5′-monophosphate phosphoribohydrolases ( 72 ), 2′-deoxyguanosine-5′-monophosphate hydrolase DNPH1 ( 73 ), and cytosine-5′-monophosphate hydrolase Blsm ( 74 ) and hydroxyl-methyl cytosine-5′-monophosphate hydrolase MilB ( 75 ) involved in the biosynthesis of the peptidyl nucleoside antifungal agents blasticidin and mildiomycin, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the low content of free bases usually cannot meet the precursor requirements for natural product biosynthesis; thus dedicated enzymes have evolved to cleave nucleosides or nucleotides. In the CGA pathway, CMP hydrolases such as BlsM and ArgD are responsible for hydrolyzing CMP to free cytosine, 15,18,19 but their homologues are not encoded in mih or apm. Among the untapped open reading frames (ORFs), BLAST analysis showed that mihD/ apmD encodes the TIGR10730 family Rossmann fold protein with unknown function.…”
mentioning
confidence: 99%